CODE-SWITCHING AND CODE-MIXING PRACTICES IN ENGLISH FOR SPECIFIC PURPOSES (ESP) COURSES - Liza Putri; Herly Nurrahmi; Akhmad Guntawan (Politeknik Negeri Media Kreatif, 2020)
This study focuses on the practices of the ESP (English for Spesific Purposes) lecturer and students toward code-switching and code-mixing (CS/CM) in the class activity. The study used descriptive qualitative method in the research. In collecting the data, the researcher shared some questionnaires and did interviews and observation. It provides the clear findings of the actual implementation of the institutional language policy on the medium of instruction in the classroom. CS/CM in both Indonesian and English languages emerged as the lecturer’s code choice in the classroom instruction. Such language practice seems not to only have undermined the role of English as the stipulated medium of instruction, but also underestimated the speech behaviour of bilinguals. It causes the conflict between the language policy and the actual use of English and Indonesian in the classroom.